RESEARCH ON PROPERTIES OF COMPOSITES BASED ON MAGNESIUM BINDERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The research is devoted to composites based on magnesium binders, which is very perspective building material in the modern construction industry. Magnesium based binders have better compatibility with organic fillers comparing to traditionally lime binder cement [1]. In this investigation two magnesium-based binders are used, such as magnesium chloride and magnesium sulphate. The aim of this study is to investigate the physical, mechanical and durability properties of composites based on magnesium binders, such as density, compressive strength, thermal conductivity and capillary water absorption, and to obtain magnesium binder that could be used to produce foamed concrete. This can be done by improving the composition of the mixture. In this framework properties of magnesium binders are analysed and how these binders can affect to the properties of magnesium based composites.